The conceptual model for the real-time navigation in Augmented Reality (AR) technology for mobile platform - Ting, Qiao Thong (2023)
The advent of augmented reality (AR) technology has revolutionized the way we navigate in the physical world. However, despite the increasing popularity of ARbased navigation apps, there is still a lack of understanding of what features and functionalities users prefer in such apps. Therefore, this research project aims to develop a conceptual model for an interactive and compelling real-time AR-based navigation experience for mobile platforms. To achieve this, the study will employ a mixed-methods approach that involves conducting a survey to collect data from the general public to better understand their preferences and requirements. The collected responses will be analyzed and interpreted to identify the key features that users prefer in real-time AR navigation apps. Additionally, an analysis of existing literature and sentiment analysis and topic modelling will be carried out on AR-based navigation apps to get an understanding of the user's preferences and vital features that contribute to a great user experience. Based on the results of the data analysis, a conceptual model for the AR-based navigation app will be proposed. The proposed conceptual model will be based on the analysis of user preferences and requirements, as well as the analysis of existing literature and apps related to AR real-time navigation on mobile platforms. The model will aim to address the identified gaps and meet the requirements of users by providing an intuitive and interactive navigation experience using AR technology. Overall, this research project aims to provide insights into the user's preferences and requirements for AR-based navigation apps on mobile platforms and to propose a conceptual model for the development of an interactive and compelling real-time ARbased navigation experience.